Global Integration Is More Important than Ever to Contain the Economic and Health Fallout and Exit the COVID-19 Pandemic Crisis - Nixon, Stewart (World Bank, Washington, DC, 2020)
As the world faces its most significant health and economic crisis in almost one hundred years, international cooperation and global integration face their own watershed moment. Large developed economies cannot escape the fallout from isolationism but have greater resources to weatherthe storm. Developing countries that rely upon large external economies, essential supply chains including food and medicine, inflows of capital and visitors, and participation in international labor markets are particularly vulnerable to a nationalistic crisis response. Global problems require coordinated global solutions to prevent disease from leading to widespread famine and death and economic contraction from disproportionately harming the most vulnerable. Global integration remains essential to developing country efforts to deal with the pandemic and recovery.Crisis-induced nationalist measures can be expected to increase the severity and duration of the economic downturn. This brief highlights the relative vulnerability of developing countries to a fractured global crisis response and how making international cooperation and exchange moredependable and crisis-proof can reduce vulnerability.